X-RAY POWDER DIFFRACTION STUDY ON THE MODULATED HIGH TEMPERATURE FORMS OF SIO2 TRIDYMITE BETWEEN 110 AND 220 °C - Graetsch H. (My University, 2001)
The crystal structure of intermediate incommensurate tridymite was refined at 150 °C from powder data. Upon cooling from above 220 °C, the basic structure with space group symmetry C2221 gradually distorted from orthorhombic to monoclinic symmetry. With decreasing temperature, the monoclinic angle γ smoothly opens up to 90.3°, while a displacive modulation with temperature-dependent wavelength develops. The 3 + 1 dimensional superspace group of the incommensurate phase is C1121ont face=symbol>aβ0). The modulation mainly consists of two sinusoidal transverse displacement waves for the silicon atoms coupled to rotations of the rigid SiO4/2trahedra. The wave vector is r=0.1192(1)a* - 0.0043(1)b* at 150 °C. Below 150 °C tridymite discontinuously transforms to another orthorhombic phase and the modulation partially locks in at the wave vector r13a*. Simultaneously, an additional incommensurate modulation with r2.0395(1)b* - 0.3882(1)c* is formed. The two-dimensional modulation does not vary significantly with the temperature.
Keywords: TRIDYMITE; SILICA; INCOMMENSURATE MODULATION; DISPLACIVE PHASE TRANSITIONS; LOCK-IN